Perancangan Sistem Informasi Customer Relationship Management (CRM) Penjualan Pupuk Dan Pestisida Pada Toko Berlian Tani - Assuary, Mutiara Fernandes; Marfalino, Hari; Surmayanti (Riset Sinergi Indonesia, 2023)
A sales information system is information using electronic media. By using this system, it is hoped that customers will be able to find out the latest product information released by Toko Berlian Tani and as the best promotional tool so that service to customers will increase. This system is also equipped with product ordering which aims to make it easier for customers to order products. By creating this system, the shop can find out the needs and desires of customers in order to establish good relationships with customers. For this reason, a CRM (Customer Relationship Management) system is needed so that creating a web-based sales information system can help customers obtain information and provide comfort and convenience for customers. The aim of this research is to provide product information and order transactions to customers quickly, practically and find out what customers need using the CRM (Customer Relationship Management) method so as to increase sales of fertilizers and pesticides at the Berlian Tani Store. Meanwhile, the creation of this system is web-based with the PHP programming language and MySQL as the database.